STRATEGI PENYEDIAAN INFRASTRUKTUR BERBASIS GREEN PORT DI PELABUHAN PANJANG KOTA BANDARLAMPUNG - Dwi Puspita, Reska; Wijayanti, Goldie Melinda; Sulistiyorini, Rahayu (Institut Teknologi Nasional Yogyakarta, 2024)
Panjang Port is a major cargo port in Indonesia. Along with the increasing demand for ports and infrastructure in Panjang Port, it can cause environmental damage. Efforts can be made by applying the green port concept to port infrastructure. However, until now, the implementation of a green port in Panjang Port has not been realized. So that this research was made with the aim of formulating an infrastructure optimization strategy that is in accordance with the application of the green port concept to infrastructure in Panjang Port. Then the data that has been obtained is then analyzed using qualitative descriptive analysis methods and SWOT analysis. Based on the literature study, the standards used are international standards and green port indicators. Based on the results of the analysis, Panjang Port is in compliance with international standards in terms of safety and security. Meanwhile, the green port indicator is not appropriate. So that the strategy formulation is based on internal factors and port external factors.